Sediment Flow Characteristics in The Upper Slope of Volcanic Landscapes With Dryland Agriculture - La Ode Hadini; Junun Sartohadi; M. Anggri Setiawan; Djati Mardiatno; Nugroho Christanto (Geosfera Indonesia, 2021)
Increasing population densities and food demands are major factors contributing to the widespread use of agricultural drylands in upper volcanic slope areas. This phenomenon poses a high risk of severe erosional events that are environmentally hazardous. Therefore, this study aims to analyze the sediment flow characteristics, based on the relationship between sediment flow and water level as well as the sediment discharge rate and soil loss. Field surveys were conducted to determine the soil measurement, slope morphology and dryland cover characteristics. The sediment flow was evaluated at the gully outlet, where 169 suspension data pairs for the modeling and 130 suspension data pairs for the validation, as well as the bed load, water level, rainfall and water flow characteristics were obtained. Tables and figures were subsequently used to represent the measurement data and analysis results for the correlation between the flow rate effects, sediment and soil loss on the water surface. The results showed that the sediment flow in volcanic landscape slopes with dryland agriculture were possibly characterized by the polynomial relationship, using the suspension discharge model, Qs=0.0322Q2+6.0625Q–1.2658. Under this condition, the average rate of soil loss in the form of sediment load and erosion rate of the catchment area occurred at 953.53 and ​​1,657.94 ton/ha/yr, respectively. Furthermore, the sediment sources in the soil loss were believed to originate from 83% of the suspended sediments and 17% bed loads. Keywords: Discharge; Dryland; Landscape; Sediment; Volcano Copyright (c) 2021 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License